Significance of clinical parameters and treatment methods for prognosis and postoperative outcome of rhegmatogenous retinal detachment - Jovanović, Đorđe; Jovanović, Vera; Karadžić, Jelena (Medicinski podmladak, 2018)
Introduction: Rhegmatogenous retinal detachment (RRD) represents separation of neurosensory retina from retinal pigment epithelium, which is sight threatening condition. The procedures for surgical management of RRD are scleral buckle and pars plana vitrectomy (PPV). Various factors may affect the success of surgery and postoperative outcome. Patients with RRD represent one of the most difficult cases for surgical treatment, while postoperative visual recovery is not always complete. The aim of this study was to analyze the methods of treatment of patients with RRD, and clinical parameters relevant for prognosis and postoperative outcome. Material and methods: Retrospective study conducted at Department of Ophthalmology, Clinical Center of Serbia, in Belgrade, from 1 January 2016 to 31 December 2016, included 203 consecutive patients hospitalized for RRD. The statistical analysis of the results on anatomical and functional outcome of operation, obtained from medical records, was carried out by t-test, Wilcoxon test and χ2 test. Results: Scleral buckle was method of choice in treatment of 56.65% patients, while PPV was performed in 43.35% of patients. Retina was successfully reapplied at 88.7% of patients treated with scleral buckle and 67% operated with PPV method. Parameters that influenced the anatomical success included: number of retinal ruptures (p = 0.022) and macular attachment (p<0.001). Statistically significant increase in postoperative visual acuity, compared to the measured preoperative visual acuity (p <0.001) was shown. Functional success was evaluated using postoperative visual acuity and depended on: macular attachment, number of retinal ruptures and type of performed surgery. Conclusion: The presented results show that patients with RRD can have a good anatomical and functional recovery, especially those cases with a single retinal rupture and macula-on. Therefore, it is important to urgently refer patients with RRD to the surgical treatment before it comes to the separation of the macula, in order to achieve better postoperative results. Keywords: rhegmatogenous retinal detachment, scleral buckle, pars plana vitrectomy, anatomical success of the operation, functional success of the operation